1996
DOI: 10.1053/jhep.1996.v23.pm0008621153
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma decreases hepatic stellate cell activation and extracellular matrix deposition in rat liver fibrosis

Abstract: Interferon gamma (IFN-gamma) inhibits in vitro the activation of hepatic stellate cells (HSC), the primary extracellular matrix-producing cells in liver fibrosis. This study was undertaken to determine in vivo the effect of IFN-gamma in the rat model of liver fibrosis induced by dimethylnitrosamine (DMN), where HSC activation represents an early response to cell injury. Rats were killed after 1 or 3 weeks of treatment with DMN, IFN-gamma, DMN + IFN-gamma, or saline. Immunohistochemistry was used to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 17 publications
3
69
0
3
Order By: Relevance
“…[10][11][12] The role of IFN-α as an antifibrotic agent has also been demonstrated in the human liver. Castilla et al 21 observed a reduction in levels of transforming growth factor (TGF) 1 mRNA expression in the liver, which correlated positively with serum PIIIP levels and histological scores for liver fibrosis in patients with chronic hepatitis C who responded well to IFN-α, suggesting that his therapy may decrease fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] The role of IFN-α as an antifibrotic agent has also been demonstrated in the human liver. Castilla et al 21 observed a reduction in levels of transforming growth factor (TGF) 1 mRNA expression in the liver, which correlated positively with serum PIIIP levels and histological scores for liver fibrosis in patients with chronic hepatitis C who responded well to IFN-α, suggesting that his therapy may decrease fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been confirmed in in-vivo experiments that IFN has an antifibrotic effect as well as an antiviral effect. [10][11][12] The aim of this study was to evaluate the antifibrotic activity of IFN-α in CH-C patients with no overt response to therapy by assessing changes in liver biopsy specimens before and after therapy, using both staging and a quantitative histological method. (Table 1) Between 1990 and 1998, 346 consecutive patients with CH-C received IFN therapy in the Gastroenterology Unit of our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Un autre méca-nisme par lequel l'alcool augmente la fibrose est son effet inhibiteur sur l'activité des cellules NK dans le foie, entre autres via la production d'IL-10 et de TGF-ß par les monocytes et les cellules étoilées du foie activées elles-mêmes [55]. En effet, les cellules NK présentent une activité antifibrosante en induisant l'apoptose des cellules étoilées du foie en cours d'activation ou senescentes [56][57][58], et en produisant l'IFN-␥, une cytokine qui induit l'arrêt du cycle cellulaire et l'apoptose des cellules étoilées du foie [59,60].…”
Section: Rôle De L'inflammation Hépatiqueunclassified
“…One of the main questions raised by hepatologists and nephrologists is whether anti-fibrotic activities known from some growth factors, e.g., hepatocyte growth factor (HGF) and interferon-c (IFN-c), may be utilized to revert fibrosis [5,6]. Therefore, clinical trials assessing the effects of IFN-c application on liver fibrosis have been initiated with mixed outcomes [7].…”
Section: Review Of the Fieldmentioning
confidence: 99%